STUDY ABOUT THE ORIGIN OF INCLUSIONS IN THE TUNDISH OF TERNIUM SIDERAR - Alejandro Martín; Juan Andres Méndez; Michel Romero; Gustavo Di Gresia; Carlos Cicutti (Tecnologia em Metalurgia, Materiais e Mineração, 2012)
For the production of steels with high quality standards is essential to know accurately the different sources that generate inclusions, in order to optimize the steelmaking practices and to minimize their frequency. The use of tracer elements in the slag has shown an effective tool to determine the origin of inclusions in continuous casting slabs. In the present study different experiences were performed using BaCO3 like a tracer in the tundish slag. Using this methodology slab samples were taken at different times of the castings. The samples were exhaustively analyzed by optical microscopy and SEM/EDS. The density, size distribution and composition of the inclusions observed were evaluated. The results of this analysis revealed the presence of inclusions with Ba in the slab during the transitory state (ladle change). For another hand, samples from the stationary state did not detect this type of inclusions. Ba inclusions occur most frequently in advanced casting sequence and in those cases where the tundish level has a weight reduction during the ladle change. These results suggest that the emulsification produced by the impact of the flow of liquid steel can generate inclusions. The effect is more pronounced when there is a greater accumulation of slag in the tundish. Finally, various tests are also performed using flow modifiers within the tundish, analyzing their impact on the generation and elimination of non-metallic inclusions